Inhibición de la corrosión del acero ASTM A192 en solución de ácido clorhídrico por el mucilago de Linum usitatissimum - Zavaleta-Gutierrez, Nilthon Emerson (2018)
In this study, the inhibition of the corrosion of ASTM A192 steel in HCl 0,5 M at temperature different, by the Linum usitatissimum mucilage, was investigated using techniques: Tafel extrapolation, linear polarization resistance, electrochemical impedance spectroscopy and electrochemical frequency modulation. The Linum mucilage acts as an optimum corrosion inhibitor of ASTM A192 steel in HCl. The average inhibition efficiency obtained with the evaluated techniques were of 84,3% at 25 °C, 89,0% at 45 °C and 91,8% at 65 °C, with a concentration of the mucilage of 1 g/l. It was found that the efficiency of inhibition and the adsorption constant increased with increasing temperature. The standard enthalpy of adsorption was positive and the apparent activation energy decreased with the increase of the concentration of the mucilage. All these parameters indicate that the adsorption of flaxseed mucilage in steel evaluated occurs through a chemical adsorption. In addition, as the temperature increases, mucilage behavior changes from an anodic inhibitor to a mixed-type inhibitor.